Different procoagulant activity of therapeutic mesenchymal stromal cells derived from bone marrow and placental decidua - Moll, Guido; Jungebluth, Philipp (Stem Cells and Development, 2015)
While therapeutic mesenchymal stromal/stem cells (MSCs) have usually been obtained from bone marrow, perinatal tissues have emerged as promising new sources of cells for stromal cell therapy.